2019
DOI: 10.7554/elife.52058
|View full text |Cite
|
Sign up to set email alerts
|

Cryo electron tomography with volta phase plate reveals novel structural foundations of the 96-nm axonemal repeat in the pathogen Trypanosoma brucei

Abstract: The 96-nm axonemal repeat includes dynein motors and accessory structures as the foundation for motility of eukaryotic flagella and cilia. However, high-resolution 3D axoneme structures are unavailable for organisms among the Excavates, which include pathogens of medical and economic importance. Here we report cryo electron tomography structures of the 96-nm repeat from Trypanosoma brucei, a protozoan parasite in the Excavate lineage that causes African trypanosomiasis. We examined bloodstream and procyclic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 91 publications
4
86
3
Order By: Relevance
“…The detailed steps of the 3D reconstruction and subtomographic averaging were previously described ( Imhof et al, 2019 ; Si et al, 2018 ). Briefly, frames from each recorded tilt series were drift-corrected and averaged with Motioncorr ( Mastronarde, 2005 ) and was further reconstructed with contrast transfer function (CTF) correction using the IMOD software package (RRID: SCR_003297 ) ( Kremer et al, 1996 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed steps of the 3D reconstruction and subtomographic averaging were previously described ( Imhof et al, 2019 ; Si et al, 2018 ). Briefly, frames from each recorded tilt series were drift-corrected and averaged with Motioncorr ( Mastronarde, 2005 ) and was further reconstructed with contrast transfer function (CTF) correction using the IMOD software package (RRID: SCR_003297 ) ( Kremer et al, 1996 ).…”
Section: Methodsmentioning
confidence: 99%
“…Only spikes of similar length were selected to ensure that each contained both NEC220 and UL25∆44 Q72A. 3D sub-tomographic averaging was completed as described ( Imhof et al, 2019 ; Si et al, 2018 ) using the PEET (particle estimation for electron tomography) software ( Nicastro et al, 2006 ). Five-fold symmetry was only applied after five-fold symmetry was apparent in the averaged structure.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work indicated that outer dynein arm-associated factors are likely important for switching between symmetric tip-to-base and asymmetric base-to-tip beats ( Edwards et al, 2018 ); however, controlling switching is distinct from the actual generation of asymmetry. Having clearly excluded the FAZ and PFR, and provided some evidence against the axoneme central pair and IC140-containing inner dynein arms being responsible for asymmetry, the most likely remaining candidate is differences between the outer doublet decorations – in particular in the region of inner arm dynein b, based on cryo-electron tomography of T. brucei ( Imhof et al, 2019 ). However, the mechanical properties of the nine-fold asymmetric outer microtubule doublets of the axoneme itself could also be important.…”
Section: Discussionmentioning
confidence: 99%
“…The anchoring of the flagellum base to the cell is also asymmetric, analogous to rootlet structures in other organisms, with lateral attachment to the cell body in the flagellar pocket via the flagellum attachment zone (FAZ) only near outer microtubule doublets 9, 1 and 2 ( Wheeler et al, 2016 ). The 9+2 axoneme itself likely also has asymmetries between outer microtubule doublets, based on recent cryo-electron tomography of the related species Trypanosoma brucei ( Imhof et al, 2019 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work indicated outer dynein arm-associated factors are likely important for 323 switching between symmetric tip-to-base and asymmetric base-to-tip beats (Edwards et al, 2018), 324 however controlling switching is distinct from the actual generation of asymmetry. The most likely 325 remaining candidate is differences between the outer doublet decorations, in particular in the region 326 of inner arm dynein b based on cryo-electron tomography of T. brucei (Imhof et al, 2019). However, 327 the mechanical properties of the nine-fold asymmetric outer microtubule doublets of the axoneme 328 itself could also be important.…”
mentioning
confidence: 99%